Antiphosphatidylethanolamine antibodies are associated with an increased odds ratio for thrombosis - Sanmarco, Marielle; Gayet, Stéphane; Alessi, Marie-Christine; Audrain, Marie; de Maistre, Emmanuel; Gris, Jean-Christophe; de Groot, Philip G.; Hachulla, Eric; Harlé, Jean-Robert; Sié, Pierre; Boffa, Marie-Claire (Thrombosis and Haemostasis, 2007)
A multicenter study was set up to evaluate the prevalence, clinical and biological significance of antiphosphatidylethanolamine antibodies (aPE) in thrombotic patients with or without the main known clinical and biological risk factors for thrombosis. APE and antibodies, defined as the laboratory criteria of antiphospholipid syndrome (APS) -lupus anticoagulant, anticardiolipin and anti-beta2-GPI antibodies were measured in 270 patients with thrombosis (234 venous and 37 arterial) and 236 matched controls. APE were found in 15% of thrombotic patients compared to 3% of controls (p<0.001) with no predominant isotype, no association with the main known clinical or biological risk factors for thrombosis neither with a type of thrombosis, arterial or venous. In a multivariate logistic regression analysis of antibodies, aPE showed the highest association with thrombosis (odds ratio [OR]: 4.2, p<0.001). Moreover, using a multivariate analysis in a case-control subgroup study on 158 patients, IgGaPE were found to be significantly associated with venous thrombosis (OR:6;p=0.005). Interestingly, 25 of the 40 aPE-positive patients (63%) were negative for the APS laboratory criteria. Most of them (21/25) had venous thrombosis, recurrent in ten of them. Four patients also suffered from early or late miscarriages. Our results underline the strength of the association between the presence of aPE and thrombosis and suggest their measurement in thrombotic patients, especially when lupus anticoagulant, anticardiolipin or anti-beta2-GPI antibodies are absent.
Keywords: thrombosis; clinical studies; antiphospholipid syndrome; Antiphospholipid antibodies; phosphatidylethanolamine